The atoning dyad: the two goats of Yom Kippur in the Apocalypse of Abraham - Orlov, Andrei A. (Studia judaeoslavica, 2016)
The study explores the eschatological reinterpretation of the Yom Kippur ritual found in the Apocalypse of Abraham where the protagonist of the story, the patriarch Abraham, takes on the role of a celestial goat for YHWH, while the text’s antagonist, the fallen angel Azazel, is envisioned as the demonic scapegoat. The study treats the application of the two goats typology to human and otherworldly figures in its full historical and interpretive complexity through a broad variety of Jewish and Christian sources, from the patriarchical narratives of the Hebrew Bible to early Christian materials in which Yom Kippur traditions were applied to Jesus’ story.0